Profesionalitas Dosen Muda Universitas Negeri Malang dalam Pelaksanaan Pembelajaran Melalui Lesson Study - Herlina Ike Oktaviani; Achmad Supriyanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
The purpose of this article is to present the results of the researchers' observations on the professionalization of UM Young Lecturers in the implementation of learning through lesson study. Lesson study has three stages, namely plan (planning), do (implementation) and see (reflection). The method used in this research is action research or classroom action research, the steps are adjusted to the lesson study steps. It is hoped that young lecturers who have little experience in teaching can add insight into learning activities through lesson study activities. Criticism, suggestions and input from observers will be a reference for improving the implementation of learning. The implementation of learning that has been discussed collaboratively with observers will have a positive impact on student activities in learning.